2012
DOI: 10.1099/ijs.0.039594-0
|View full text |Cite
|
Sign up to set email alerts
|

Parvibaculum hydrocarboniclasticum sp. nov., a mesophilic, alkane-oxidizing alphaproteobacterium isolated from a deep-sea hydrothermal vent on the East Pacific Rise

Abstract: An aerobic, alkane-oxidizing bacterium, designated strain EPR92 T , was isolated from hydrothermal fluids that had been collected from a deep-sea vent on the East Pacific Rise (at 96 509 N 1046 179 W). The cells of the novel strain were Gram-staining-negative rods that measured approximately 1.4 mm in length and 0.4 mm in width. Strain EPR92T grew at 20-40 6C(optimum 35 6C), with1.0-5.0 % (w/v) NaCl (optimum 2.5 %), and at pH 4.0-8.5 (optimum pH 7.5). The generation time under optimal conditions was 63 min. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Among these, 42 genera were significantly affected by willows at both contamination levels, and the 24 bacterial and fungal genera among those are listed in Supplementary Table S2. Among the genera consistently activated by willows at both contamination levels, some were previously reported as having interesting characteristics for phytoremediation, for instance, Methylibium petroleiphilum is involved in aromatic hydrocarbon and methyl tertbutyl ether degradation (Nakatsu et al, 2006), Mesorhizobium is a well-known genus involved in nitrogen fixation, some species are resistant to metals (Vidal et al, 2009;Huang et al, 2010) and can degrade acetonitrile (Feng and Lee, 2009), some Variovorax species display plant growth promoting activities and are able to degrade various contaminants (Han et al, 2011) and Parvibaculum species are able to degrade linear carbon chains, including alkanes (Schleheck et al, 2004;Rosario-Passapera et al, 2012). Some other genera showed contrasting responses to willows when exposed to different concentrations of contaminants (Supplementary Table S2).…”
Section: Competition and Cooperationmentioning
confidence: 99%
“…Among these, 42 genera were significantly affected by willows at both contamination levels, and the 24 bacterial and fungal genera among those are listed in Supplementary Table S2. Among the genera consistently activated by willows at both contamination levels, some were previously reported as having interesting characteristics for phytoremediation, for instance, Methylibium petroleiphilum is involved in aromatic hydrocarbon and methyl tertbutyl ether degradation (Nakatsu et al, 2006), Mesorhizobium is a well-known genus involved in nitrogen fixation, some species are resistant to metals (Vidal et al, 2009;Huang et al, 2010) and can degrade acetonitrile (Feng and Lee, 2009), some Variovorax species display plant growth promoting activities and are able to degrade various contaminants (Han et al, 2011) and Parvibaculum species are able to degrade linear carbon chains, including alkanes (Schleheck et al, 2004;Rosario-Passapera et al, 2012). Some other genera showed contrasting responses to willows when exposed to different concentrations of contaminants (Supplementary Table S2).…”
Section: Competition and Cooperationmentioning
confidence: 99%
“…These major cellular fatty acids of strain GYP-11 T are similar to those of members of the genera Parvibaculum (Lai et al, 2011;Rosario-Passapera et al, 2012), Tepidicaulis (Takeuchi et al, 2015) and Parvularcula (Arun et al, 2009;Yu et al, 2013;Li et al, 2014). However, members of the genera Parvibaculum, Tepidicaulis and Parvularcula are characterized by cyclo C 19 : 0 v8c (12.1-35.8 %), C 18 : 1 v7c/v6c (87.3 %) and C 16 : 0 (10.0-24.1 %), respectively.…”
Section: G Wang and Othersmentioning
confidence: 66%
“…Growth of Parvibaculum lavamentivorans DS-1 T on MAP was observed, but was much slower than strain GYP-11 T . Finally, strain GYP-11 T could be distinguished from all members of the genus Parvibaculum (Lai et al, 2011;Rosario-Passapera et al, 2012) by its inability to utilize alkane. Other cultural, physiological and biochemical properties of strainGYP-11 T are listed in Table 1 and in the genus and species descriptions.…”
Section: G Wang and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptothrix phylotypes were already detected in Table 1 Geochemical composition, organic acid concentrations and pH measured in the medium during the culture time nd not determined, bd below the detection limit (bd is 10 µM for H 2 S) a The day when pH falls down to 3. Alphaproteobacteria were detected at the end in D21 and in the solid fraction collected at the end of the culture, including sequences closely related to the Parvibaculum sp., sharing 99 % of similarity with Parvibaculum indicum (strain P31T) (8 % of the total clones), a mesophilic strain isolated from deep seawater collected in the SouthWest Indian Ridge (Lai et al 2011) and 99 % with Parvibaculum hydrocarboniclasticum, a mesophilic strain isolated from hydrothermal fluid (Rosario-Passapera et al 2012). In previous enrichment cultures, it was shown that Parvibaculum lavamentivorans, formerly described as an aerobic strain, is able to grow autotrophically in anaerobic condition, oxidizing Fe(II) using nitrates as electron Fig.…”
Section: Active Microbial Communities In the Initial Flange Sample Anmentioning
confidence: 99%